An Equivalent Dipole-Moment Method Based Multilevel Fast Multipole Algorithm for Dielectric Objects - Chen, Xinlei; Gu, Changqing; Ding, Ji; Deng, Xiaoqiao; Niu, Zhenyi; Li, Zhuo (Applied Computational Electromagnetics Society Journal (ACES), 2022)
An equivalent dipole-moment method (EDM) based multilevel fast multipole algorithm (MLFMA), namely EDM-MLFMA, is proposed for the electromagnetic scattering from threedimensional (3D) dielectric objects. In this scheme, the MLFMA is employed to accelerate the interactions of equivalent dipoles in the far regions by expanding the 3D dyadic Green’s function into a multipole expression. The memory requirement and CPU time of the conventional EDM are reduced from O(N2 ) to O(N log N) , where N is the number of unknowns. Numerical results are presented to validate the efficiency and accuracy of this method.